Mucinous neoplasia of appendix: imaging and its relevance to management - K. Lathiya, Hardikkumar; Gupta, Priya; Kamat, Ritesh D.; Patankar, Roy S. (International Journal of Research in Medical Sciences, 2023)
Appendiceal mucocele is a rare pathology of the appendix that can present with non-specific symptoms. Therefore, imaging evaluation is essential for accurate diagnosis and proper management. To document importance of pre-operative imaging, we reviewed the scans, reports, and clinical data of nine patients with appendiceal mucocele who were treated at our institute. We also studied the literature on CT findings, histopathology, surgical management, prognosis, and recent guidelines for appendiceal mucocele. We suggest that pre-operative imaging can aid surgeons in selecting the most appropriate treatment plan for each patient, resulting in better outcomes. Certain critical imaging features, such as mural nodularity, irregular wall thickening, lymphadenopathy, cecal involvement, presence of free mucus, or pseudomyxoma peritonei, can alert surgeons to prepare for frozen section and an appropriate surgical approach. In conclusion, we recommend pre-operative imaging as a crucial tool for the diagnosis and management of appendiceal mucocele. Its use in identifying critical imaging features can help surgeons decide on the best surgical approach for each patient and ultimately lead to better outcomes.